Incidence of tuberculosis in patients with immune-mediated diseases undergone biological therapy: A 10-year observational study in a high-burden region of northeastern Brazil - Rosinete Maria dos Santos Guimarães; Claudia Diniz Lopes Marques; Ulisses Ramos Montarroyos; Carolina Santos Guimarães; Jaqueline Alves da Silva; Linaldo Francisco Silva Filho; Vanessa Medeiros; Irassandra Rooze Pereira Uchôa Cavalcanti de Aquino; Rafael Dhalia; Edmundo Pessoa Lopes; Carlos Alexandre Antunes de Brito (PLoS ONE, 2026)
Biological therapies are critical in the management of Immune-Mediated Diseases (IMDs), yet their use is linked to adverse effects, including an elevated risk of Tuberculosis (TB), a significant health issue in endemic regions like Brazil. This study aimed to assess the incidence of TB among patients with IMDs in rheumatology, gastroenterology, and dermatology who received biological therapy in Pernambuco between 2013 and 2023. A total of 8,623 patients were analyzed, with 90.7% diagnosed with rheumatologic diseases, 5.6% with gastroenterological diseases, and 3.7% with psoriasis. In the descriptive analysis, frequency distributions and medians with interquartile ranges were reported, and Relative Risk (RR) was calculated to compare tuberculosis occurrence across IMD groups. The overall TB incidence was 2.1%, highest in gastroenterological patients (4.7%) compared to rheumatologic (2.0%) and psoriasis patients (1.3%) with a risk ratio (RR) of 2.4 for the group of gastroenterological diseases (p < 0.001). No significant differences in TB frequency were detected before (1.16%) or during (0.97%) the use of biological therapy, nor among drug classes, except for a slightly higher incidence with infliximab (2.6%). The absence of differences between the other anti-Tumor Necrosis Factor (anti-TNF) drugs and other cytokine inhibitors suggests that TB incidence might be influenced by environmental exposure in endemic regions. Pulmonary TB was the predominant form (80.8%), and pleural TB emerged as the most frequent extrapulmonary manifestation. The results underscore the need for extensive regional studies to elucidate TB risks in IMD patients and refine treatment guidelines for immunobiological therapies.